The emperor's new clothes: favourite tales - Daly, Audrey; Long, Sally Andersen, Hans Christian (Ladybird Place of publication not identified, 1993)
Two rascally weavers convince the emperor they are making him beautiful new clothes, visible only to those fit for their posts, but during a royal procession in which he first wears them, a child whispers that the emperor has nothing on